Exploring the Impact of Bilingualism on Semantic and Phonological Neuropsychological Tasks in Adults - Seyede Zohre Mousavi; Azar Mehri; Saman Maroufizadeh (Journal of Rehabilitation Sciences and Research, 2024)
Background: Numerous studies have yielded conflicting results concerning the disparities in verbal (semantic and letter) fluency between monolingual and bilingual individuals. Given the linguistic variations among bilinguals and the influence of cultural differences on language, this study examined verbal fluency in Kurdish and Azari bilinguals and compared it with that of Farsi monolinguals.Methods: This cross-sectional study involved 30 Farsi monolingual students, 28 Kurdish-Farsi bilinguals, and 29 Azari-Farsi bilinguals. The study utilized semantic (fruits and animals) and letter fluency tasks (/f/, /a/, and /s/). Each bilingual participant was instructed to perform the verbal fluency tasks twice: once in their native language and once in Farsi.Results: In both fluency tasks, bilinguals demonstrated superior performance in Farsi compared to their mother languages (Azari and Kurdish) (P <0.001). Furthermore, no significant differences were observed between bilinguals and monolinguals in the formal language of their community (Farsi).Conclusion: The formal language in Iran (Farsi) predominates among bilingual individuals. This is likely because the educational system and formal writing are conducted in Farsi. Bilinguals typically use their native language only for conversations within their native context and with their peers.